Student's guide: new sem prep / Nor Haniza Hasan - Hasan, Nor Haniza (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2023)
The start of the new academic year is quickly approaching. How many students are aware that it is important to ensure they are adequately prepared for a new semester? Among the preparations they should be ready for are daily timetable, budget planning, and syllabuses overviewing. Forming a timetable is a priority as it will aid the students to utilize their time efficiently throughout the semester. Class hours, studying, and leisure should be listed and sorted accordingly. Missing lectures and burning the midnight oil to do last-minute homework can be avoided since the students have proper planning on which activities they need to fulfill by the hour. Planning monthly budgeting is another preparation to be done. Students should list their essential and non-essential expenses. Therefore, they can adjust their allowance for spending and save some aside in case of emergencies. It also can prevent them from being spendthrift by spending the money on unnecessary items.